Radiofrequency ablation of a fascicular tachycardia after orthotopic cardiac transplantation. Issue 4 (1st April 1998) - Clarke, N; Mason, M; Paul, V
Abstract : A 51 year old male received an orthotopic transplant because of end stage ischaemic heart disease. The donor was a healthy male teenager with no history of arrhythmias or other cardiac conditions. The patient presented with haemodynamically stable tachycardia and dyspnoea five weeks post-transplant. The ECG showed a regular tachycardia of 140 beats/min with a right bundle branch block morphology, left axis deviation, and a QRS duration of 135 ms. There were independent P waves, capture, and fusion beats confirming the diagnosis of ventricular tachycardia. Endomyocardial biopsy showed moderate focal rejection that was thought to be responsible for the arrhythmia. During the following six months the patient had recurrent tachyarrhythmias; on each occasion the ECG morphology was the same and there was no cellular rejection. The patient continued to have frequent hospital admissions with ventricular tachycardia requiringdc cardioversion despite the empirical use of amiodarone, sotalol, disopyramide, and procainamide. Eighteen months after transplantation the diagnosis of fascicular tachycardia was suspected by ECG morphology and supported by successful termination with intravenous verapamil. The arrhythmia was successfully managed by radiofrequency ablation. This patient shows that arrhythmias following transplantation are not always related to rejection, and that other potentially reversible causes should be considered, particularly when the ECG during arrhythmia conforms to a classic configuration.